UJI ADAPTASI VARIETAS UNGGUL BARU TERHADAP WERENG HIJAU DAN PENYAKIT TUNGRO DI KABUPATEN MERAUKE, PROVINSI PAPUA - Sudarsono Sudarsono; Dini Yuliani (Agric, 2017)
Tungro is one of the important diseases in rice plants caused by two types of viruses were rod virus (rice tungro bacilliform virus) and spherical virus (rice tungro spherical virus) that was transmitted by the green leafhopper (GLH) Nephotettix virescens. The purpose of this study to determine the adaptation of new improved varieties against GLH and tungro disease in Merauke, Papua Province. Research conducted at Tanah Miring District, Merauke, Papua Province between February and June 2010. The study was a randomized block design with three replications. The treatment consisted of 11 varieties, namely Inpari 1, Inpari 2, Inpari 3, Inpari 4, Inpari 5 Merawu, Inpari 6 Jete, Inpari 7 Lanrang, Inpari 8, Inpari 9 Elo, Inpari 10 Laeya, and Ciherang. Observations included the intensity of tungro and GLH population density at the age of rice plants of 1, 2, 3, and 4 weeks after planting (WAP). In addition, it was observed also the yield components of rice. The results showed that the GLH population density and the intensity of tungro disease was not significantly different at the 11 varieties tested. GLH attack had been found in 1 WAP with an average population density of 4.18 individual/20 single swing. GLH increases with the age of the rice crop with an average population density in 2 WAP (20 individual), 3 WAP (103.27 individual), and 4 WAP (154.15 individual) per 20 single swing. Tungro disease intensity in 11 varieties began were found in 3 WAP on average by 0.16% and increased at 4 WAP on average by 0.28%. Varieties significant effect on yield components such as plant height, panicle length, number of total grain/panicle, percentage of filled grain, 1000 grain weight and productivity except the number of panicles/clump.